The Impact of Verbal Violence by Peers on Career Decision-Making Self-Efficacy and Career Adaptability among Senior Secondary School Students - Lusia Cella Ramadaning; Diniy Hidayatur Rahman; Muslihati Muslihati (Indonesian Journal of Counseling and Development, 2026)
Adolescence is a critical stage for identity formation, social development, and career preparation. In Islamic boarding schools (pesantren), intensive peer interactions offer vital social support but can expose students to verbal violence like ridicule. While research often examines social support in career development, peer verbal violence remains understudied as a psychosocial risk factor for Career Decision-Making Self-Efficacy (CDMSE) and career adaptability in these unique settings. Grounded in Social Cognitive Career Theory (SCCT) and Career Construction Theory, this quantitative correlational study investigated the relationships among peer verbal violence, CDMSE, and career adaptability. Utilizing purposive and stratified random sampling, data were collected from 156 senior high school students via validated Likert-scale instruments and analyzed using Spearman’s rank correlation. The findings revealed that peer verbal violence was significantly and negatively associated with CDMSE (r = -0.831, p < .001) and career adaptability (r = -0.913, p < .001). Increased exposure to verbal violence correlated with lower career decision-making confidence and reduced adaptability to future career transitions. These results support the SCCT proposition that adverse social environments act as contextual barriers undermining self-efficacy, which directly links to career adaptability within Career Construction Theory. This study contributes to career development literature by extending these theories to the continuous peer environment of pesantren. Consequently, educational institutions must strengthen anti-bullying policies, cultivate positive peer dynamics, and design comprehensive counseling interventions to enhance students' career self-efficacy and adaptability